INTERPRETAÇÃO E EXISTÊNCIA: AS PROXIMIDADES ENTRE HERMENÊUTICA E VIDA NO PENSAMENTO CONTEMPORÂNEO E O RETORNO AO TEXTO EM PAUL RICOEUR - FERREIRA, LEONARDO MAGAL DE. (2017)
Considering the close relationship between hermeneutics and existence that took place at the end of the nineteenth century and lasted for the most part in the following century, our dissertation aims to present, in a first moment, how such proximity contributed to the displacement of the textual element, the more evident hermeneutic characteristic. Through the conceptual analysis that underpins this work, we find a gradual detachment in the unique and exclusive treatment of the text in favor of life in the thought of Friedrich Schleiermacher, Wilhelm Dilthey, Martin Heidegger and Hans-Georg Gadamer. From these postulates, we will try to demonstrate next how Paul Ricoeur differentiates itself to the extent that defends the return to the textual sphere as the main task of hermeneutics through the narrative text. Ricoeur finds in this modality a rich enlargement of the relation between interpretation and existence due to the mimetic process that governs the constitution of all type of narrative. This author observes that all textual construction is born in life, in the world of action and is completed in life, now of the reader, now of the interpreter, thus contributing to the formation of a narrative identity from everything we read and interpret. Thus, we shall first discuss the exposition in chapters one and two of the main moments of change of perspective carried out by the authors mentioned above. The conclusion we come to and which constitutes chapter three, addresses the changes brought by Ricoeur in his defense of the text as a link between hermeneutics and life by seeing it as an intrinsic element of existence and impossible to ignore.